PHYSICAL, CHEMICAL, AND SENSORY CHARACTERISTICS OF INSTANT NOODLES WITH PURPLE SWEET POTATO FLOUR (IPOMOEA BATATAS L. POIR) SUBSTITUTION AT VARIOUS CONCENTRATIONS - Rostiati Rostiati; Abdul Rahim; Pratiwi Pratiwi (AGROLAND The Agricultural Sciences Journal (e-Journal), 2020)
Instant noodles are generally made from wheat flour as raw material. The abunandce of purple sweet potatoes can substitute the wheat flour. The purpose of this study was to determine the effect of substitution of purple sweet potato flour at various concentrations on the physical, chemical, and sensory test of instant noodles. The research was conducted at the Agro-Industry Laboratory, Faculty of Agriculture, Tadulako University, from June to December 2019. The experiment was arranged using a completely randomized design (CRD) with 1 factor, namely the substitution of instant noodle purple sweet potato flour at a concentration of 0.5, 10, 15, 20, 25, and 30%. The treatments were repeated three times so that 21 experimental units were obtained. For the sensory test using a randomized block design (RBD) with 30 panelists. The parameters of the observation consisted of the loss of solids due to cooking, water absorption, water content, ash content, and sensory tests. The results of research on substitution of purple sweet potato flour at various concentrations gave the best effect at a concentration of 30% on instant noodles produced based on physical, chemical, and sensory properties. With the highest loss of solids due to cooking, the absorption of instant noodles decreased as the concentration of purple sweet potato flour increased. Instant noodle moisture content constant tendency at each treatment. The ash content of instant noodles increased with increasing concentration of purple sweet potato flour and the sensory properties of color, texture, aroma, and taste of the instant noodles increased with the increasing concentration of purple sweet potato flour on the hedonic scale category. Noodles substituted with purple sweet potato flour can be consumed as instant noodles, such as those circulating in the market.